Layanan Konseling Kelompok Untuk Mengurangi Perilaku Interaksi Sosial Disosiatif Siswa - Amana, Laely Itsna; Kurniawan, Kusnarto; Mugiarso, Heru (Indonesian Journal of Guidance and Counseling: Theory and Application, 2019)
The purpose of this study was to observe the influence of group counseling services on dissociative social interaction grade VIII SMP Negeri 3 Ungaran. This type of research is a research experiment one group pre-test post-test design. This research is conducted six times with 8 students of the subject. Data collection was done with scale dissociative social interaction to students directly. Analytical techniques descriptive analysis of the data using the percentage and wilcoxon test. The results showed that there was a change after giving treatment group counseling, that is from data analysis calculation of Wilcoxon test table, the smallest number of levels or T arithmetic value is 0. While Ttable for n=4 with the level of error 5% is 4. Then it can be seen that the value (T count